Teachers’ Perspective of their Role and Student Autonomy in the PBL Context in China - Li, Huichun; Du, Xiangyun (International Journal of Learning, Teaching and Educational Research, 2015)
The traditional role of the teacher confronts many challenges by an increasing number of educational initiatives that highlight student-centered learning in China, since the teacher’s role is in great need of transformation from instructor to facilitator. Therefore, it is quite necessary to examine how teachers perceive their role within a context in the process of making educational innovations. This study relies on two Chinese universities which are changing their educational approach from lecture-based learning to Problem Based Learning (PBL). We examine how the teachers perceive their role in a PBL context. In particular, we are mainly concerned with teachers’ attitudes towards student learning autonomy in PBL contexts. The data is mainly relied upon in-depth interviews of the teachers who participate in PBL practice from the two cases. When focusing on how teachers perceive student learning autonomy, we can note three major patterns. In general, Chinese teachers have a tendency to maintain high interference in student learning process even though they admit the value of giving student learning autonomy. This study further indicates a dilemma between teachers’ intention to encourage students to learn on their own and their tendency to maintain their directive role in the educational processes.